Evaluation of Chicken Skin with Fat as Sunflower Oil Replacer on Quality Aspects of Patties Prepared from Spent Female Buffalo Meat - Gurunathan, Kandeepan (International Journal of Livestock Research, 2023)
The poultry industry offers certain valuable by-products such as chicken skin with fat that have vast applications in meat food product development. Vegetable oils are commonly used for emulsion-based meat products due to their ease of storage and handling during processing. The research was undertaken to replace vegetable oil with animal fat for improving the nutritional value and sensory attributes of buffalo meat patties to ensure the viable use of animal by-products in meat products. The buffalo meat patties were replaced with chicken skin with fat (CSF) for sunflower oil (SFO) during the emulsion formation. The results of the cooked products have shown significantly (P<0.05) higher values for pH, moisture, shear force, appearance, flavor, texture, and juiciness in chicken skin with fat-added buffalo meat patties. Whereas the yield, emulsion stability, increase in height, fat, cholesterol, and energy were significantly (P<0.05) higher in sunflower oil-added buffalo meat patties. Hence it is concluded that the replacement of sunflower oil (SFO) by chicken skin with fat (CSF) in buffalo meat patties is a healthy alternative since it produced lower fat, cholesterol, and energy with improved appearance, flavor, texture, and juiciness in meat product.